General Population Norms for the Functional Assessment of Cancer Therapy – Kidney Symptom Index (FKSI) - Butt, Zeeshan (2012)
BACKGROUND: Metastatic renal cell cancer is associated with poor long-term survival and has no cure. Traditional clinical endpoints are best supplemented by patient-reported outcomes designed to assess symptoms and function. We obtained normative data on the NCCN - Functional Assessment of Cancer Therapy – Kidney Symptom Index (NFKSI) to aid in score interpretation and planning of future trials. METHODS: General population data were obtained from 2000 respondents, who completed the NFKSI-19, as well the SF-36 and the PROMIS-29, both general health status measures. Basic demographic and self-reported comorbidity data were also collected. RESULTS: The sample was 50% female, 85.7% Caucasian, with an equal distribution across age bands 18–75+. Most respondents (62.8%) had more than a high school education and reported an ECOG performance status of normal activity without symptoms (63.4%). Score distributions on the NFKSI-19, its subscales, and individual items are summarized. CONCLUSIONS: The NFKSI-19 and its subscales now have scores for the general US population, allowing comparability to generic questionnaires such as the SF-36 and PROMIS-29. These data can be used to guide treatment expectations and plan future comparative effectiveness research using the scales.